Recanalisation of a congenital extrahepatic portosystemic shunt previously attenuated with cellophane banding in a cat. Issue 2 (August 2018) - Crowley, James; Foo, Timothy; Boland, Lara; Brunel, Laurencie
Case summary: A congenital extrahepatic portosystemic shunt was attenuated with commercial roll cellophane banding in a cat and postoperative liver changes were monitored using CT angiography (CTA). The patient clinically improved after cellophane banding, characterised by resolution of hepatic encephalopathy, weight gain, reference interval (RI) bile acid stimulation tests, as well as CTA-documented increased liver size, increased hepatic vasculature and shunt attenuation. Six months later the cat re-presented with recurrence of clinical signs and increased bile acids. CTA confirmed recanalisation of the shunt. Shunt attenuation was repeated using pure cellophane banding and nearly complete closure of the shunt was later documented by CTA. Seven months later, recanalisation was again documented via CTA and associated with clinical signs and increased bile acids. Complete ligation of the shunt was achieved using a polypropylene ligature and a titanium ligating clip. At long-term follow-up, the cat was clinically well, and bile acids and biochemistry were within the RIs. Relevance and novel information: This is the first report of CTA-documented recanalisation of an extrahepatic portosystemic shunt previously attenuated with cellophane banding. Recanalisation should be considered as a differential for recurrence of hepatic encephalopathy following cellophane banding.